Brief communication: Omega-3 essential fatty acid supplementation and erythrocyte oxidant/antioxidant status in rats - Iraz, Mustafa; Erdogan, Hasan; Ozyurt, Birsen; Ozugurlu, Fikret; Ozgocmen, Salih; Fadillioglu, Ersin (My University, 2005)
Fish oil contains large amounts of essential omega-3 fatty acids, such as eicosapentaenoic and docosahexaneoic acids, which are building structures of cell membranes. The goal of this study was to elucidate the effects of dietary omega-3 fatty acid supplementation on the oxidant/antioxidant status of erythrocytes in rats. The malondialdehyde (MDA) and nitric oxide (NO) levels and the catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GSH-PX) activities were assayed in erythrocytes of male Wistar albino rats after 30 days of dietary supplementation with fish oil (0.4 g/kg/day). Erythrocyte CAT activity in the treated group was increased in comparison with the control group. Erythrocyte MDA and NO levels were lower in the treated group than the controls. Erythrocyte GSH-Px and SOD activities did not differ significantly in the 2 groups. Negative correlations were found between SOD and CAT activities, and between SOD and GSH-Px activities in the treated group. In conclusion, omega-3 fatty acid supplementation helps to prevent lipid peroxidation and to safeguard erythrocytes from oxidative injury. Dietary supplementation with omega-3 fatty acids might possibly protect tissues from oxygen free radical injury in the various diseases in which the oxidant/antioxidant defense mechanisms are disturbed. © 2005 by the Association of Clinical Scientists, Inc.
Keywords: Fish oil; Lipid peroxidation; Nitric oxide; Omega-3 essential fatty acids; Oxidant/antioxidant st